High‐Voltage‐Driven Surface Structuring and Electrochemical Stabilization of Ni‐Rich Layered Cathode Materials for Li Rechargeable Batteries. Issue 23 (4th May 2020) - Song, Seok Hyun; Cho, Moses; Park, Inchul; Yoo, Jong‐Gyu; Ko, Kyung‐Tae; Hong, Jihyun; Kim, Jongsoon; Jung, Sung‐Kyun; Avdeev, Maxim; Ji, Sungdae; Lee, Seongsu; Bang, Joona; et al.
Abstract: Layered lithium–nickel–cobalt–manganese oxide (NCM) materials have emerged as promising alternative cathode materials owing to their high energy density and electrochemical stability. Although high reversible capacity has been achieved for Ni‐rich NCM materials when charged beyond 4.2 V versus Li + /Li, full lithium utilization is hindered by the pronounced structural degradation and electrolyte decomposition. Herein, the unexpected realization of sustained working voltage as well as improved electrochemical performance upon electrochemical cycling at a high operating voltage of 4.9 V in the Ni‐rich NCM LiNi0.895 Co0.085 Mn0.02 O2 is presented. The improved electrochemical performance at a high working voltage at 4.9 V is attributed to the removal of the resistive Ni 2+ O rock‐salt surface layer, which stabilizes the voltage profile and improves retention of the energy density during electrochemical cycling. The manifestation of the layered Ni 2+ O rock‐salt phase along with the structural evolution related to the metal dissolution are probed using in situ X‐ray diffraction, neutron diffraction, transmission electron microscopy, and X‐ray absorption spectroscopy. The findings help unravel the structural complexities associated with high working voltages and offer insight for the design of advanced battery materials, enabling the realization of fully reversible lithium extraction in Ni‐rich NCM materials. Abstract : Structural and electrochemical stabilization of Ni‐rich LiNi x Co y Mn1− x − y O2 (NCM) materials under high‐voltage battery operation is demonstrated. The improved electrochemical performance at a high working voltage at 4.9 V is attributed to the removal of the resistive Ni 2+ O rock‐salt surface layer, which stabilizes the voltage profile and improves retention of the energy density during electrochemical cycling.